Numerical Investigation of Reinforced Concrete Beam Due to Shear Failure - Piscesa, Bambang; Alrasyid, Harun; Prasetya, Dwi; Iranata, Data (IPTEK The Journal for Technology and Science, 2020)
This paper investigates the possibility of using a multi-surface plasticity model to predict shear failure in reinforced concrete beams. The analysis is carried out using the in-house software called 3D-NLFEA. The constitutive model for the concrete material is based on the plasticity-fracture model, which had previously developed to simulate the behavior of concrete cover spalling in reinforced concrete columns. To obtain the asymmetric shear failure pattern, random material properties imperfection for each meshed element is used. Two beams available in the literature are investigated and compared with the analysis results using 3D-NLFEA. From the comparisons, excellent agreement between the analysis and the test result was obtained. 3D-NLFEA can predict the peak load accurately. The peak load prediction only varies 2.19% for beam OA1 and 3.28 % for beam OA2, and it was lower than the test results. The failure crack patterns also show a typical diagonal crack extension from the support to the loading steel plate.